Recent Advances in the Synthesis of Aromatic Azo Compounds - Meng-Yun Zhao; Yue-Feng Tang; Guo-Zhi Han (Molecules, 2023)
Aromatic azo compounds have -N=N- double bonds as well as a larger π electron conjugation system, which endows aromatic azo compounds with wide applications in the fields of functional materials. The properties of aromatic azo compounds are closely related to the substituents on their aromatic rings. However, traditional synthesis methods, such as the coupling of diazo salts, have a significant limitation with respect to the structural design of aromatic azo compounds. Therefore, many scientists have devoted their efforts to developing new synthetic methods. Moreover, recent advances in the synthesis of aromatic azo compounds have led to improvements in the design and preparation of light-response materials at the molecular level. This review summarizes the important synthetic progress of aromatic azo compounds in recent years, with an emphasis on the pioneering contribution of functional nanomaterials to the field.